2015
DOI: 10.1016/j.neuron.2015.06.035
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Shared Cortical Variability

Abstract: SummaryNeuronal responses of sensory cortex are highly variable, and this variability is correlated across neurons. To assess how variability reflects factors shared across a neuronal population, we analyzed the activity of many simultaneously recorded neurons in visual cortex. We developed a simple model that comprises two sources of shared variability: a multiplicative gain, which uniformly scales each neuron’s sensory drive, and an additive offset, which affects different neurons to different degrees. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
337
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(383 citation statements)
references
References 57 publications
35
337
11
Order By: Relevance
“…Even worse, in some cases, one can reach opposite conclusions about how correlations affect information when analyzing small rather than large populations. For instance, Lin et al (2015) considered a code in which correlations are beneficial rather than detrimental for small populations. However, in their code, correlations reduce information when a larger population is considered (Figure 3 c ).…”
Section: Estimating Linear Fisher Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Even worse, in some cases, one can reach opposite conclusions about how correlations affect information when analyzing small rather than large populations. For instance, Lin et al (2015) considered a code in which correlations are beneficial rather than detrimental for small populations. However, in their code, correlations reduce information when a larger population is considered (Figure 3 c ).…”
Section: Estimating Linear Fisher Informationmentioning
confidence: 99%
“…Two recent studies have reported that information is affected by global fluctuations, based on simulating (Lin et al 2015) or analyzing (Arandia-Romero et al 2016, Pachitariu et al 2015, using Shannon information) small ensembles. However, in large populations, only differential correlations can make information saturate.…”
Section: Sources Of Correlationsmentioning
confidence: 99%
“…Trial-to-trial variability in how neurons fire to the same stimulus tends to be correlated (Averbeck and Lee, 2003; Deweese and Zador, 2004; Lin et al, 2015; Shadlen and Newsome, 1998) and these noise correlations may increase or decrease the ability to decode information from ensemble activity (Averbeck and Lee, 2006; Averbeck et al, 2006), and may or may not affect overall coding capacity of the network (Abbott and Dayan, 1999; Narayanan et al, 2005; Shamir and Sompolinsky, 2006; Zohary et al, 1994). Typically, the importance of these noise correlations is assessed by shuffling each cell’s trial-by-trial activity and testing whether there are any differences in the ability to discriminate stimuli based off of the observed versus shuffled ensemble activity patterns (Averbeck and Lee, 2006; Latham and Nirenberg, 2005).…”
Section: What the Ensemble Code Reveals About The Nature Of Neural Rementioning
confidence: 99%
“…Being comparable in clinical characteristics and lesion size, the fav-REC and poorREC groups differed by strength of functional connectivity, which might be explained by possible group differences in (1) more critical damage of white matter tracts 67 or cortical areas 30 that was not captured by our analysis, (2) premorbid cognitive/neural reserves influencing how the brain responds to injury, 68 and (3) interindividual functional and anatomical variability. 69,70 Nonetheless, functional connectivity reflected the network capacity for early reorganization and recovery, and provided prognostic information for neglect patients at a very early stage. This information derived 2 to 3 days poststroke might eventually translate to better outcomes, 37 indicating patients requiring more intensive rehabilitation in the early stage.…”
Section: Contralesional Functional Homologues and Predictors Of Recoverymentioning
confidence: 99%